THE EFFECT OF PICTURE AND PICTURE METHOD IN WRITING DESCRIPTIVE TEXT AT SEVENTH GRADE STUDENTS OF MTSN 1 PADANGSIDIMPUAN IN 2023/2024 ACADEMIC YEAR - Kamisah Kamisah; Srimaharani Tanjung; Lolo Rosa Lubis (Institut Pendidikan Tapanuli Selatan, 2024)
The aims of the research is to know the effect of using picture and picture method in students writing descriptive text at the seventh grade of MTsN 1 Padangsidimpuan. To analyze the data researcher used the experimental method. The data were collected by observation, interview and Test. The population of this research were all of the seventh grade students of MTsN 1 Padangsidimpuan. The sample were 72 students which are taken by cluster random sampling technique. The data that has been collected were analyzed by using statistic analysis is used to prove the hypothesis that the researcher used t test formula. The research has been found the mean score of writing descriptive text before applying picture and picture method was 60.8 and after was 68.1. The result of the analyzed data shows that the score of ttest was 6.09.The score of ttable at 5 % significant level of 35 was 2.03. After finding the value of the calculation and ttable, both of scores are compared. It was found that t test is higher than ttable(ttest>ttable= 6.09 > 2.03). It means that there was any significant effect of using picture and picture method in writing descriptive text at seventh grade students of MTsN 1 Padangsidimpuan.